A Decoupling Structure of Controllable Reactor of Transformer Type - Yu He; Huatai Chen (Institute of Advanced Engineering and Science, 2015)
In order to make controllable reactor of transformer type (CRT) working of safety, reliable and compensation effect is obvious, the principle of “high impedance, weak coupling” must be satisfied in the design of CRT structure. The magnetic integration technology used in the design of the ontology of CRT in this paper, a decoupling integrated core structure is proposed. This paper also calculates the leakage reactance and current of decoupling structure. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6724